2019
DOI: 10.3390/ani9121138
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Leucine Supplementation Restores Serum Glucose Levels, and Modifying Hepatic Gene Expression Related to the Insulin Signal Pathway in IUGR Piglets

Abstract: Simple Summary: Intrauterine malnutrition may compromise the size and structure of fetal organs and tissues, which leads to lower birth weight and a slower rate of growth after weaning. Intrauterine growth restriction/retardation (IUGR) impairs pancreas function, resulting in the decreased glucose levels in serum. Leucine, one of branched chain amino acids, is an essential amino acid and the substrate of protein synthesis. Leucine also acts as a major regulator of hormone signal transduction, like insulin. Die… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 60 publications
0
3
0
Order By: Relevance
“…In the present study Leu increased plasma levels of CCK but not of GLP-1, indicating a potentially stronger response from the proximal (where CCK is mainly produced by I cells of the enteroendocrine system) than the distal (the main site of production of GLP-1 by L-cells) small intestine ( Tian et al, 2019 ). Leu showed a less sustained effect on CCK secretion suggesting that the long-term impact on appetite may be partially explained by the release of other gut peptides or post absorptive signals associated with blood branched-chain AA (BCAA) imbalances interacting with the CNS ( Lynch et al, 2006 ; Kwon et al, 2019 ; Zhang et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…In the present study Leu increased plasma levels of CCK but not of GLP-1, indicating a potentially stronger response from the proximal (where CCK is mainly produced by I cells of the enteroendocrine system) than the distal (the main site of production of GLP-1 by L-cells) small intestine ( Tian et al, 2019 ). Leu showed a less sustained effect on CCK secretion suggesting that the long-term impact on appetite may be partially explained by the release of other gut peptides or post absorptive signals associated with blood branched-chain AA (BCAA) imbalances interacting with the CNS ( Lynch et al, 2006 ; Kwon et al, 2019 ; Zhang et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…High dietary levels of Leu and Ile showed a strong anorexigenic effect potentially mediated by CCK and GLP-1 in pigs ( Millet et al, 2015 ; Kwon et al, 2019 ; Tian et al, 2019a ; Müller et al, 2022 ). The activation of long-term satiety signals such as leptin and insulin have also been described associated to dietary BCAA in pigs ( Lynch et al, 2006 ; Zhang et al, 2019 ). Gut hormones have been involved in satiety resulting in an increase in the intermeal interval, which may explain the decreased feed intake in the Leu and Ile-gavaged pigs ( Overduin et al, 2014 ; Williams et al, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…Unexpectedly, contrary to the growth promotion effect of leucine on normal suckling piglets, administration of leucine led to decreased production performance in IUGR piglets during suckling period, accompanied by lower plasma amino acid levels, changes in plasma biochemical parameters and the expression of amino acid transporters in the jejunum. Previous studies on weaned IUGR piglets (14–35 d of age) fed a basal diet supplemented with 0·3–0·35 % l -leucine have shown that l -leucine improves growth performance and glycolipid metabolism (32,43) . These evidence suggests that l -leucine is beneficial to IUGR piglets in response to weaning stress.…”
Section: Discussionmentioning
confidence: 99%